Efikasi Diri, Ketidaknyamanan Terhadap Tugas, dan Konformitas Teman Sebaya Sebagai Prediktor Prokrastinasi Akademik - Qomariyah, Nunung; , Dr. Sri Lestari S.Psi, M.Si (2016)
This research is a quantitative research that aims to examine the role of self-efficacy, task aversivenesand konformita peers as a predictor of academic procrastination. The population in this study were students of the faculty of engineering and psychology from a university that is located in Surakarta, as many as 432 students. These samples included 130 mhasiswa consisting of 74 male and 56 female, with a random sampling techniques. Measuring instrument using a scale. Hasi showed that there was a significant relationship between self efficacy, task aversivenes, and conformity to peer academic procrastination. Taken together self efficacy, task aversivenes, and knformitas peers accounted for 85.4% of the academic procrastination. Self-efficacy in the low category, the effective contribution of 80.5% and a negative correlation direction. Inconvenience to the task tergoong moderate, with 4.3% and the effective contribution towards positive relationship. Conformity peers is high, the effective contribution of 0.6% and a positive correlation direction. Academic procrastination in middle category. Judging from gender and faculty, there are differences in the level of academic procrastination. Judging from the period of study, the level of procrastination in students with study period> 5th higher than students with study period <5th. The implication of this study is to evaluate candidates to prevent academic procrastination behavior among students.